Treatment Options for Pregnant Women With Ovarian Tumors. Issue 6 (1st July 2014) - Mancari, Rosanna; Tomasi-Cont, Nicoletta; Sarno, Maria Anna; Azim, Hatem A.; Franchi, Dorella; Carinelli, Silvestro; Biglia, Nicoletta; Colombo, Nicoletta; Peccatori, Fedro Alessandro
Abstract : Diagnosis of ovarian mass during pregnancy is a rare event. Treatment of ovarian malignancies during pregnancy depends on histology, grade, stage, and gestational weeks. When possible, surgical excision is indicated, and sometimes, fertility-sparing surgery is recommended. Administration of systemic treatment before or after surgery is indicated as in nonpregnant women. Preliminary data suggest that platinum salts and taxanes are safe during pregnancy. Management of ovarian tumors in pregnancy requires a multidisciplinary approach to guarantee an optimal treatment for the mother and the fetus.